The impossibility of capitalist markets in higher education - Marginson, Simon (Journal of education policy, 2013)
For more than two decades, governments around the world, led by the English-speaking polities, have moved higher education systems closer to the forms of textbook economic markets. Reforms include corporatisation, competitive funding, student charges, output formats and performance reporting. But, no country has established a bona fide economic market in the first-degree education of domestic students. No research university is driven by shareholders, profit, market share, allocative efficiency or the commodity form. There is commercial tuition only in parts of vocational training and international education. While intensified competition, entrepreneurship and consumer talk are pervasive in higher education, capitalism is not very important. At the most, there are regulated quasi-markets, as in post-Browne UK. This differs from the experience of privatisation and commercialisation of transport, communications, broadcasting and health insurance in many nations. The article argues that bona fide market reform in higher education is constrained by intrinsic limits specific to the sector (public goods, status competition), and political factors associated with those limits. This suggests that market reform is utopian, and the abstract ideal is sustained for exogenous policy reasons (e.g. fiscal reduction, state control, ordering of contents). But, if capitalist markets are clearly unachievable, a more authentic modernisation agenda is needed.